The Impact of Nurse-Led Interventions on Patient Outcomes in Chronic Disease Management: A Comprehensive Review - ALMUTIRI, YAHYA FAHD; alotiby, Abdulkareem mousem; Al-Dosari, Shayea Saad Mubarak; almalhan, Fisal fahad hamad; ALBOGAMI, ABDULLAH HALAL; Hijraf, Saud Ali; Aldawsari, Ali Abdullah; qohman, Misfer husieen (Journal of Posthumanism, 2024)
Chronic diseases represent a significant global health burden, accounting for approximately 71% of all deaths worldwide. Nurse-led interventions have emerged as a promising approach to improve patient outcomes and reduce healthcare costs. This paper provides a comprehensive review of current evidence regarding the effectiveness of nurse-led interventions in managing chronic diseases, including diabetes mellitus, hypertension, and chronic obstructive pulmonary disease (COPD). Through systematic analysis of peer-reviewed literature and empirical research, this paper demonstrates that nurse-led interventions significantly improve patient adherence to treatment regimens, enhance clinical outcomes, reduce hospital readmission rates, and improve quality of life. Key findings indicate that nurse-led clinics, patient education programs, and remote monitoring systems are particularly effective in chronic disease management. The paper discusses the mechanisms through which these interventions work, identifies barriers to implementation, and proposes recommendations for practice and policy. Implications for nursing practice, healthcare administration, and future research are explored to advance the integration of nurse-led models in clinical settings.